Legal position of the young farmer in Poland in the light of the European Parliament Resolution of 29 May 2018 - Litwiniuk, Przemysław (Przegląd Prawa Rolnego, 2020)
The European Parliament Resolution of 29 May 2018 on the implementation in the EU of CAP tools for young farmers after the 2013 reform draws the attention of EU bodies and European institutions as well as the governments of the Member States to the significant problem of adequate forms and safeguards for the position of young farmers provided for in EU legislation and national regulations. The article presents the reasons for the adoption of the resolution and the recommendations addressed to the Council, the European Commission, the Court of Auditors and the governments and parliaments of the Member States. An analysis of the instruments developed to support young farmers in Poland and facilitate a generational change in rural areas was conducted and it has been found that despite certain unquestionable achievements to date, Polish legal solutions are still largely ineffective, fragmentary and incomplete.